2016
DOI: 10.1155/2016/9458396
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mesenchymal Stem Cells and Platelet‐Rich Plasma on the Bone Healing of Ovariectomized Rats

Abstract: We evaluated the efficacy of platelet-rich plasma (PRP) in combination with allogeneic bone marrow mesenchymal stem cells (BMSCs) for the treatment of osteoporotic bone defects in an ovariectomized rat model. By day 42 after injury, in vivo microcomputed tomography (micro-CT) imaging revealed that bone defects of control rats and ovariectomized rats treated with PRP and BMSCs were completely repaired, whereas those of ovariectomized rats treated with PRP or BMSCs alone exhibited slower healing. Histological da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 25 publications
5
44
1
Order By: Relevance
“…The tibial defect model was established as reported previously. 50 , 51 A 1.5-mm-diameter tibial defect was made in all SD rats approximately 5 mm from the proximal tibial growth plate by a hollow drill. The same leg was used for each group.…”
Section: Methodsmentioning
confidence: 99%
“…The tibial defect model was established as reported previously. 50 , 51 A 1.5-mm-diameter tibial defect was made in all SD rats approximately 5 mm from the proximal tibial growth plate by a hollow drill. The same leg was used for each group.…”
Section: Methodsmentioning
confidence: 99%
“…Risk of bias of animal studies was high for almost all the examined studies. Among the 13 included in vivo studies, three for PLT functions during OP and 10 for PLT derivatives in OP, 10 of them have not declared the method of sequence generation [41,42,[49][50][51][52][53]56,57], in one study the method was unclear [55] and in the remaining two studies the method of sequence generation was clearly declared [40,58]. The majority (n = 7) of the studies showed that groups were similar concerning baseline characteristics (i.e., age, weight, sex) and two studies showed that allocation was adequately concealed [40,58].…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
“…PRP-induced osteogenesis was confirmed by simultaneously up-regulating osteogenesis-promoting genes RUNX2, OPN and OCN and down-regulating adipogenesis regulators such as PPAR-γ2 and leptin in bone marrow cells of PRP treated animals [50]. Allogenic BMSCs in combination with PRP were also used for the treatment of OP bone defects in an OVX rat model showing that bone defects of OVX rats treated with PRP and BMSCs were completely repaired, whereas those treated with PRP or BMSCs alone exhibited slower healing [55]. In addition, higher expression levels of RUNX2, OSX, and OPN were found in rats treated with PRP and BMSCs [55].…”
Section: Platelet Derivatives In Osteoporosismentioning
confidence: 95%
See 2 more Smart Citations